2008
DOI: 10.1002/eji.200737590
|View full text |Cite
|
Sign up to set email alerts
|

Forced overexpression of either of the two common human Foxp3 isoforms can induce regulatory T cells from CD4+CD25 cells

Abstract: The forkhead/winged helix transcription factor (Foxp3) is expressed as two different isoforms in humans: the full-length isoform (Foxp3FL) and an alternative-splicing product lacking the exon 2 (Foxp3DE2). We here studied the cellular distribution of Foxp3 isoforms by quantitative PCR and evaluated the functional outcome of retroviral transduction of Foxp3FL and Foxp3DE2 genes into CD4 + CD25 -cells. In PBMC, both isoforms were preferentially expressed in CD4 + CD25 hi cells. In single-cell-sorted and expanded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 36 publications
7
70
3
Order By: Relevance
“…[24,25]. On the other hand, transduction of Foxp3 can induce the expression of CD25, CTLA-4, and GITR, and it exerted suppressive activity in vitro [7,26]. Hence, Foxp3 expression was also detected in our study.…”
Section: Discussionsupporting
confidence: 54%
“…[24,25]. On the other hand, transduction of Foxp3 can induce the expression of CD25, CTLA-4, and GITR, and it exerted suppressive activity in vitro [7,26]. Hence, Foxp3 expression was also detected in our study.…”
Section: Discussionsupporting
confidence: 54%
“…The absence of FOXP3 in patients with immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome (IPEX) or scurfy mutation results in a lack of functional Tregs (Bennett et al, 2001). Overexpression of FOXP3 in conventional T cells leads the cells to become a Treg phenotype with suppressive activity, leading to a state of immune deficiency (Aarts-Riemens et al, 2008). In fact, changes in Foxp3 expression on CD4 ϩ CD25 ϩ Tregs were also …”
Section: Downloaded Frommentioning
confidence: 99%
“…Studies in humans confirmed that FOXP3 is expressed by tTreg cells and crucially controls their function and maintenance [7], as also demonstrated by the observation that high and stable expression of FOXP3 in human Teff cells leads to the acquisition of Treg phenotype and functions [14,15].…”
Section: Role Of Foxp3 In Treg Cellsmentioning
confidence: 75%